Analisis Kestabilan Lereng Gambut Pesisir Utara Bengkalis - Tabah Miftahudin; Syawal Satibi; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Peat soil slope stability is influenced by soil properties, the depth of the water table and the effect of loading or surcharges. Land conversion on areas can cause changes in peatland hydrological balance that led to a decrease in ground water level and causing slope failure. This study analyzes slope stability modeling based on the limit equilibrium principle by Morgenstern-Price method. The current peat slope collapse in the Bengkalis Island North Coast continue to occur by progressive despite to the decline in groundwater levels provide increasing peat slope safety factors.Keywords: Peat slope stability, groundwater level, limit equilibrium slope analysis